Ethiopathogenic factors influencing the development of basal cell carcinoma - Roine Alberto Pena-Olivera; Ana Laura Navarro-Baldellot; Leydiani Espín-Guerra (Universidad Médica Pinareña, 2021)
Introduction: basal cell carcinoma is a cutaneous neoplasm of high incidence, characterized by slow growth and low metastatic capacity.